Interference Effects on the Square and Circular Cross-Sectional High-Rise Buildings Under Turbulent Flows (International Journal of Architectural Engineering Technology, 2022)
Estimating the wind-induced responses of high-rise buildings requires a detailed investigation of wind force characteristics and structural dynamics, especially when an existing neighboring building has an equivalent volume at adjacent locations. The interference effects caused by such an adjacent building may seriously alternate the wind loading characteristics on the target building and further affect its responses to safety or habitability evaluation. This research investigates the interference effects on the wind-induced responses of high-rise buildings under turbulent boundary layer flows based on a series of wind tunnel tests. This study mainly concerns three disturbance factors to the interference effects: the approaching turbulent flows, the interference locations, and two typical section shapes of the concerned high-rise buildings. Results show that the terrain effect, the interference location effect, and the shape effect of both the principal and the interfering buildings significantly change the interference mechanism to the aerodynamic force and the estimated responses. The aerodynamic and the response interference factors defined in this study have shown distinct different patterns, indicating the interfered resonant response plays a vital role in dominating the interference mechanism. Finally, discretized maps with a satisfactory 0.5B × 0.5B grid resolution under statistical assumptions are proposed as examples for future codification works.
Keywords: High-rise building; Interference effect; Interference factor; Aerodynamic force; High-frequency force balancer